Aristotelian Practical Philosophy from Melanchthon to Eisenhart: Protestant Commentaries on the Nicomachean Ethics 1529-1682 - Svensson, Manfred (Reformation & Renaissance review, 2019)
The place of the Nicomachean Ethics as the standard textbook for the teaching of ethics remained unaltered during the Reformation and post-Reformation era. As a result, close to forty commentaries on this work were published in Protestant territories between 1529 and 1682. Most of these commentaries have previously been listed in studies of the history of Aristotle's reception, but only a very small number have been the object of more specific study. This article presents a survey of this tradition in both its Lutheran and Reformed trajectory, and it deals with the elements of the medieval and the Renaissance traditions of Aristotelian commentary that permeate Protestant Aristotelianism. Finally, it discusses the way in which the Aristotelian understanding of practical philosophy was received by these early modern Protestants.